PEROXIDASE ISOZYME IDENTIFICATION OF SOME RICE GENOTYPES IN M1 GENERATION UNDER DROUGHT STRESS LEVEL OF -0.03 MPa - Herwibawa, Bagus; Haryanto, Totok Agung Dwi; Sakhidin, Sakhidin (Faculty of Agriculture University of Brawijaya and Indonesian Agronomic Assossiation, 2014)
The effort to fulfill the need of rice through the improvement of dryland productivity can be viewed as a more environmentally-friendly way. This research used 36 rice genotypes in M1 generation that were grown hydrophonically under drought stress level of -0.03 MPa. The identifications were conducted based on peroxidase isozyme marker. The isozyme patterns in zymogram were binary-coded by visual scores for each genotype, based on the thickness and the number in the appearance of bands on certain migration distance. The migration distances were measured based on values of Rf. The similarity coefficients were calculated using Diceâs coefficient that were used to construct dendrogram using the UPGMA employing the SAHN from the NTSYSpc 2.02. The results showed that the most resistant genotype under drought stress was R-4, and the genetic relationships among the genotypes were divided into two main groups, aromatic and non-aromatic group, in which some genotypes experienced the reduced levels of aromatic character (R-8 and R-9) and the drought resistance character (IU-2, IU-3, IU-4, IU-5, IU-6, IU-7, and IU-8), but there were some genotypes to able to improve the resistance under drought stress (R-2, R-3, R-5, R-6, R-7, IT-4, IT-5, and IT-7).Â Keywords:Â drought resistance, gamma irradiation, peroxidase isozyme, rice, sodium azide